2012
DOI: 10.1111/j.1365-2265.2011.04303.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of recombinant human growth hormone therapy in adults with Prader–Willi syndrome: a meta‐analysis

Abstract: In PWS adults, rhGH therapy led to decreased body adiposity and increased LBM without changes in BMI or lipids. There was a small increase in fasting glucose and trends towards higher insulin and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
87
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 38 publications
11
87
0
Order By: Relevance
“…Most individuals with PWS, but not all, are deficient in GH and studies that were initially focused on improving growth have not only demonstrated this effect, but also improvements in metabolism, body composition, behavior and cognition (38)(39)(40)(41)(42)(43)(44). However, GH therapy on occasion can be associated with significant side effects, such as the stimulation of adenoid tissue leading to obstructive sleep apnea so it should be used carefully in the treatment of PWS.…”
Section: Clinicaltrialsgov [Nct]: Id Number Nct01725152)mentioning
confidence: 99%
“…Most individuals with PWS, but not all, are deficient in GH and studies that were initially focused on improving growth have not only demonstrated this effect, but also improvements in metabolism, body composition, behavior and cognition (38)(39)(40)(41)(42)(43)(44). However, GH therapy on occasion can be associated with significant side effects, such as the stimulation of adenoid tissue leading to obstructive sleep apnea so it should be used carefully in the treatment of PWS.…”
Section: Clinicaltrialsgov [Nct]: Id Number Nct01725152)mentioning
confidence: 99%
“…Therefore, age appropriate screening protocols for conditions, such as sensory impairment and various forms of cancer (with the possible exception of PAP smears in women without a history of sexual activity), should also be offered to adults with PWS 9) . Growth hormone therapy might also have positive effects on functional decline and energy levels of older people with PWS 12) . Staff should be provided with knowledge on syndrome-specific age related characteristics and should be trained on how to integrate this in existing practices 9) .…”
Section: Issues In General Healthmentioning
confidence: 99%
“…In addition, Oto et al observed that cessation of GH therapy in young PWS patients worsened BMI after 6 months 34) . In 2011, a meta-analysis of eight studies, comprising a total of 134 adults with PWS on GH treatment, was published 38) . All the studies, which ranged from 12 to 72 months, showed that GH treatment improved body composition, with an increase in lean body mass and a reduction in total body fat and subcutaneous and visceral fat 38) .…”
Section: Role Of Growth Hormonementioning
confidence: 99%